2005
DOI: 10.1353/dem.2005.0037
|View full text |Cite
|
Sign up to set email alerts
|

Do conditional cash transfers influence migration? A study using experimental data from the Mexican progresa program

Abstract: Prior research on Mexican migration has shown that social networks and economic incentives play an important role in determining migration outcomes. We use experimental data from PROGRESA, Mexico's primary poverty-reduction program, to evaluate the effects of conditional cash transfers on migration both domestically and to the United States. Our study complements a growing body of literature aimed at overcoming longstanding hurdles to the establishment of causal validity in empirical studies of migration. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 29 publications
5
65
0
10
Order By: Relevance
“…These findings confirmed those of other Oportunidades evaluations regarding the contraceptive behavior and fertility of female beneficiaries aged 14-49 and women aged 20-49 who gave birth within three years of baseline (Huerta and Hernández 2000;Stecklov et al 2005) and contrasted with what others found among women aged 15-49 (Hernández Prado et al 2005) after two years of program exposure. The current study found a small yet significant effect of the program on contraceptive use among titulares in 2000, in accordance with the small increase (2 percent; p = 0.01) that Stecklov and his colleagues (2006) found.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings confirmed those of other Oportunidades evaluations regarding the contraceptive behavior and fertility of female beneficiaries aged 14-49 and women aged 20-49 who gave birth within three years of baseline (Huerta and Hernández 2000;Stecklov et al 2005) and contrasted with what others found among women aged 15-49 (Hernández Prado et al 2005) after two years of program exposure. The current study found a small yet significant effect of the program on contraceptive use among titulares in 2000, in accordance with the small increase (2 percent; p = 0.01) that Stecklov and his colleagues (2006) found.…”
Section: Discussionsupporting
confidence: 88%
“…We offer two possible explanations for the program's surprising lack of effect on birth spacing, given that contraceptive use-one of the primary proximate determinants of fertility (Bongaarts and Potter 1983)-increased. First, male migration to the United States appears to have decreased as a result of the Oportunidades program (Stecklov et al 2005), and with more men at home, suggest Stecklov and his colleagues (2006), there may be a greater frequency of intercourse and, consequently, an increased demand for contraception without a corresponding decline in fertility. Second, the lack of correspondence between contraceptive use and birth spacing might have been a consequence of our narrow definition of contraceptive use-namely, use of modern methods.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, the program led to a decrease or no impact on domestic migration but a small increase in international migration (Angelucci 2012;Stecklov et al 2005), 2 while in Nicaragua there was an increase in migration of males across a wide age range (Winters, Stecklov and Todd 2006). 3 In related literature in South Africa, Ardington, Case, and Hosegood (2009) use longitudinal data to examine the effect of a household member gaining or losing an old-age pension on labor migration of prime age adults living in the same household.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, men from central-western Mexico were more likely to emigrate to the United States in years when the Mexican interest rate increased, which could reflect a substitution between the U.S. wages and costly loans in Mexico (Massey and Espinosa 1997). Research works on cash transfers, which may function as an alternative source of capital to bank loans or migrant remittances, find inconsistent patterns in relation to migration (Angelucci 2011(Angelucci , 2012Stecklov et al 2005).…”
Section: Conclude Thatmentioning
confidence: 99%